Adjuvant therapy for high‐risk cutaneous squamous cell carcinoma: 10‐year review. Issue 9 (7th June 2021) - Newman, Jason G.; Hall, Mary A.; Kurley, Sarah J.; Cook, Robert W.; Farberg, Aaron S.; Geiger, Jessica L.; Koyfman, Shlomo A.
Abstract: Standard of care for high‐risk cutaneous squamous cell carcinoma (cSCC) is surgical excision of the primary lesion with clear margins when possible, and additional resection of positive margins when feasible. Even with negative margins, certain high‐risk factors warrant consideration of adjuvant therapy. However, which patients might benefit from adjuvant therapy is unclear, and supporting evidence is conflicting and limited to mostly small retrospective cohorts. Here, we review literature from the last decade regarding adjuvant radiation therapy and systemic therapy in high‐risk cSCC, including recent and current trials and the role of immune checkpoint inhibitors. We demonstrate evidence gaps in adjuvant therapy for high‐risk cSCC and the need for prognostic tools, such as gene expression profiling, to guide patient selection. More large‐cohort clinical studies are needed for collecting high‐quality, evidence‐based data for determining which patients with high‐risk cSCC may benefit from adjuvant therapy and which therapy is most appropriate for patient management.